Income and malaria: Evidence from an agricultural intervention in Uganda - Yao Pan; Saurabh Singhal (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
We exploit a spatial discontinuity in the coverage of an agricultural extension program in Uganda to causally identify its effects on malaria. We find that eligibility for the program reduced the incidence of malaria by 8.8 percentage points, with children and pregnant women experiencing most of these improvements. An examination of the underlying mechanisms indicates that an increase in income and the resulting increase in the ownership and usage of bednets is the most likely candidate driving these effects. Taken together, these results signify the importance of liquidity constraints in investments for malaria prevention and the potential role that agricultural development can play in easing it.
Keywords: I15; O12; Q16; 330; malaria; agricultural extension; regression discontinuity; Uganda